Concentrations in Plasma, Urinary Excretion, and Bactericidal Activity of Linezolid (600 Milligrams) versus Those of Ciprofloxacin (500 Milligrams) in Healthy Volunteers Receiving a Single Oral Dose - WAGENLEHNER, Florian M. E; WYDRA, Stephan; ONDA, Hajime; KINZIG-SCHIPPERS, Martina; SÖRGEL, Fritz; NABER, Kurt G (Antimicrobial Agents and Chemotherapy, 2003)
Classifications Services AAC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue AAC About AAC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AAC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0066-4804 Online ISSN: 1098-6596 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AAC .asm.org, visit: AAC